Analisis Sentimen dan Jaringan Komunikasi Respon Ketua BPOM Peny Lukito Kasus Gagal Ginjal Akut Pada Anak dalam akun Youtube Kompas.com - Abadi, Medi Trilaksono Dwi; Sagita, Virginia Ayu; Shovmayanti, Noor Afy (Jurnal Paradigma, 2023)
A crisis can endanger the reputation and performance of an institution or agency, especially government property. One of the causes of a crisis is the emergence of unexpected events with wide-reaching impacts that occur quickly. This also elicited various responses from various circles. Facing the development of information technology, especially social media, crisis situations can also be influenced by various responses from netizens that appear on social media. Indonesia is experiencing a crisis situation related to the phenomenon of health problems in the form of acute kidney failure that occurs in children which is allegedly caused by the dangers of cough syrup-type drugs by the dangerous chemicals ethylene glycol and deethylene glycol. Responding to this phenomenon, Chairperson of the Food and Drug Supervisory Agency (BPOM) Mrs. Peny Lukito held regular press conferences with the main agenda related to the current situation in handling this case. This study aims to look at the formation of a communication network and sentiment analysis from netizens towards the response of the BPOM leadership using a social media network analysis approach on the Youtube channel with the Kompas.com account broadcast live online. The findings in this study are that Peny Lukito as the head of BPOM received negative responses from netizens because they considered him negligent and transferred responsibility to other parties.